The Problem Of The Subject And Object In Jalaluddin Rumi’s Theory Of Knowledge (Eurasian Journal of Humanities and Social Sciences, 2025)
This article provides an in-depth analysis of the philosophy of Jalal al-Din Rumi and his Sufi ideas. Jalal al-Din Rumi is one of the great representatives of Eastern philosophy, and his works are enriched with Sufi concepts. Rumi encourages individuals to understand their inner world, acquire true knowledge, and connect with God. His teachings encompass essential concepts such as spirituality, love, religious tolerance, and consciousness. Rumi’s ideas hold significant importance in the education of modern youth and serve to promote peace and tolerance. The article also highlights the relevance of Rumi’s legacy in contemporary society